Design and construction of a multifunctional disinfection robot - Tuleshov, Amandyk; Jamalov, Nutpulla; Imanbayeva, Nurbibi; Rakhmatulina, Ayaulym (Eastern-European Journal of Enterprise Technologies, 2022)
This paper proposes a robot designed for automated routine or emergency disinfection in closed premises. The robot is related to the combined type robots. The robot consists of two functional parts: a universal mobile platform (lower part) and a disinfector (upper part), which, if necessary, can be freely moved by personnel on 4 wheels. In the initial position, the upper part of the disinfection robot is at the charging station. The mobile robot drives up to the disinfector, «hooks» it (puts it on itself) and moves along the planned route. The upper part of the disinfector will have its own independent intelligent system, separate from the mobile robot, which, when a person is recognized, stops liquid disinfection: in this case, the UV lamps turn through 180°, the cylindrical body closes and ventilation of the disinfected air from the enclosed space is turned on. In addition, liquid disinfection is only enabled when detecting beds, tables and chairs. With the spray nozzles located at a height of 400 mm, the disinfector can carry out a simultaneous combined treatment of rooms with equipment and furniture, including high-quality processing of the lower surfaces of tables, chairs and beds. To improve the functional characteristics of robotic disinfectors and to simplify their design, a multifunctional robotic disinfector has been proposed. It was found that the result is achieved by the fact that in a multifunctional disinfection robot containing a mobile cart with an autonomous positioning and navigation system, a disinfection platform with a disinfection liquid spraying system and UV lamps with reflectors installed on it, the disinfection platform will have its own autonomous control and power systems.